Uranium and thorium in the Precambrian basement of western Canada. I. Abundance and distribution - Burwash, R. A.; Cumming, G. L. (Canadian Journal of Earth Sciences, 1976)
Delayed neutron activation analyses of 182 core samples from the basement of the western Canada sedimentary basin give mean values of 4.13 ppm U and 21.1 ppm Th. These values are almost twice the published values for the Shield as a whole. Replicate analyses of a composite sample of all cores indicates an analytical precision of ±1% for uranium and ±7% for thorium.Histograms of number of samples vs. U and Th values indicate a negatively skewed frequency distribution. Analysis of composite samples prepared from a large number of hand specimens may tend to conceal this skewed nature. Mean abundance values will also be influenced by the form of the U and Th frequency distributions.Trend surface analysis, with smoothing to reduce the effect of high or low single sample values, indicates two 'highs' common to both U and Th. The helium-producing area around Swift Current, Saskatchewan is associated with a high U–Th plutonic complex. A linear belt trending northeast from Edmonton appears to be a Hudsonian metamorphic belt in which U and Th have been concentrated. Several local concentrations of U or Th are found in the Peace River Arch of northern Alberta.